The soulmate [compact disc, unabridged] - Hepworth, Sally (Macmillan Audio, 2023)
There's a cottage on a cliff. Gabe and Pippa's dream home in a sleepy coastal town. But their perfect house hides something sinister. The tall cliffs have become a popular spot for people to end their lives. Night after night Gabe comes to their rescue, literally talking them off the ledge. Until he doesn't. When Pippa discovers Gabe knew the victim, the questions spiral ... Did the victim jump? Was she pushed? And would Gabe, the love of Pippa's life, her soulmate ... lie? As the perfect facade of their marriage begins to crack, the deepest and darkest secrets begin to unravel.